Practical Implications of Empirically Studying Moral Decision-Making - Heinzelmann, Nora; Ugazio, Giuseppe; Tobler, Philippe (Frontiers in Neuroscience, 2012)
When considering morality, at least three core questions come to mind: Which is the best normative theory? Which theory best describes moral decision-making? Why do people not behave the way they ought to behave? While the first question resides in the normative domain and concerns the way agents ought to make moral decisions, the second resides in the empirical domain and concerns the way we actually make those decisions. Both questions have been treated with some detail previously. Here we focus on the third question, which is a pragmatic one, reaching both into the normative and descriptive domains of morality. It naturally leads to another question: Can we narrow the gap between what people are morally required to do and what they actually do? Two main problems usually keep us from acting and judging in a morally decent way a) we make mistakes in moral reasoning, and b) even when we know how to act and judge, we still fail to meet the requirements due to personal weaknesses. We describe possibilities with which overcoming such shortcomings, as suggested by findings from neuroscience, economics, and psychology. Whether such possibilities should be implemented is a normative question that we put up for discussion